The benchmarking book a how-to-guide to best practice for managers and practitioners - Stapenhurst, Tim (Elsevier/Butterworth-Heinemann, 2009)
With growing demands for increased operational efficiency and process improvement in organizations of all sizes, more and more companies are turning to benchmarking as a means of setting goals and measuring performance against the products, services and practices of other organizations that are recognized as leaders. The Benchmarking Book is an indispensable guide to process improvement through benchmarking, providing managers, practitioners and consultants with all the information needed to carry out effective benchmarking studies. Covering everything from essential theory to important consi.
Keywords: Benchmarking (Management); elektronické knihy; electronic books